Reversing Lewis acidity from bismuth to antimony. Issue 71 (11th August 2021) - Sharma, Deepti; Balasubramaniam, Selvakumar; Kumar, Sandeep; Jemmis, Eluvathingal D.; Venugopal, Ajay
Abstract : Investigations on the boundaries between the neutral and cationic models of (Mesityl)2 EX (E = Sb, Bi and X = Cl −, OTf − ) have facilitated reversing the Lewis acidity from bismuth to antimony. Abstract : Investigations on the boundaries between the neutral and cationic models of (Mesityl)2 EX (E = Sb, Bi and X = Cl −, OTf − ) have facilitated reversing the Lewis acidity from bismuth to antimony. We use this concept to demonstrate a higher efficiency of (Mesityl)2 SbOTf over (Mesityl)2 BiOTf in the catalytic reduction of phosphine oxides to phosphines. The experiments supported with computations described herein will find use in designing new Lewis acids relevant to catalysis.